In command of guardians : executive servant leadership for the community of responders - Russell, Eric J. (Springer, 2017)
First responders in the fire, emergency, and police agencies work in high-risk, critical situations, and require effective leadership. Using the approach of Servant Leadership, Dr. Russell explains how executive level/chief officers can lead their teams by helping responders develop and perform as highly as possible and meet the needs of their followers. To bring the power of this philosophical approach towards leadership to life, this book demonstrates how its many aspects come together as a system, in order to strengthen the community of emergency responders. Featuring case studies and questions as meditative exercises, the book offers readers a rich learning experience. Targeted at fire chiefs, fire commissioners, police chiefs, and Emergency Medical Service, and other first responders, this book will have a positive impact on these organizations and the communities they serve. It is also useful for training aspiring executive level leaders/chief officers.
Keywords: Servant leadership -- United States.; Emergency management -- United States.; Emergencies.; Assistance in emergencies.; Fire departments.; Police administration.; Medical emergencies.; United States.; elektronické knihy; electronic books